Chronic Idiopathic Vitritis: Ultrastructural Properties of Bacteria-Like Bodies within Vitreous Leukocyte Phagolysosomes - Johnson, Lewis A.; Wirostko, Emil (American journal of clinical pathology, 1986)
In chronic idiopathic vitritis (CIV) corticosteroid treatment failures, vitrectomy is beneficial. Searching for vitreous microbial agents, 14 vitrectomy specimens from 11 corticosteroid-failing CIV patients were inoculated into numerous in vitro cultural systems; Gram's-, Giemsa-, periodic acid-Schiff- (PAS), and Dieterle-stained centrifuged sediment smears were studied with the light microscope; and the sediment was examined electron microscopically. None of the specimens demonstrated in vitro growth. However, by light microscopy the smears of ten specimens from 8 of the 11 patients demonstrated, in a background of predominantly mononuclear leukocytes, a few polymorphonuclear leukocytes with minute cytoplasmic Gram's variable coccal bodies. By electron microscopy those ten specimens showed morphologically similar 0.5-0.7-micron, thick-walled, coccal-shaped, bacteria-like bodies and 0.03-micron electron-dense spheric particles within polymorphonuclear leukocyte phagolysosomes. The results suggest that CIV vitreous, sterile by contemporary laboratory technics, commonly demonstrates these phagolysosomal bacteria-like bodies. Innovative attempts should be made to cultivate these bacteria-like bodies. Animal pathogenicity studies, using these vitreous specimens as inocula, have been conducted. The results of that investigation will be the subject of another report.